Granulomatous pigmented purpuric dermatosis: Clinical and histopathologic findings in a series of nine cases. (22nd March 2022) - Matter, Alexandra Valeska; Kolm, Isabel; Kempf, Werner
Abstract: We report the largest case series to date of granulomatous pigmented purpuric dermatosis (GPPD), a rare variant of pigmented purpuric dermatoses (PPD). GPPD can cause diagnostic difficulties as it can be mistaken clinically and histopathologically with numerous inflammatory and infectious dermatoses or even cutaneous T‐cell lymphoma. We compared the histopathological findings of nine cases of GPPD with a control group consisting of 10 randomly selected PPD of other subtypes. GPPD seems to predominantly affect the lower extremities of adult male patients; a clear association with hyperlipidemia or other systemic conditions could not be confirmed. Histopathologically, GPPD is characterized by a dermal histiocyte‐rich interstitial infiltrate with or without granuloma formation, thickened capillaries, extravasated erythrocytes, and/or hemosiderin deposits. In contrast to other forms of PPD, the inflammatory infiltrate of GPPD can extend to the mid or deep dermis and the admixed lymphocytic infiltrate is mainly composed of CD8+ T‐cells.